DETERMINAN KEPATUHAN DALAM PENERAPAN UNIVERSAL PRECAUTION - Puput Lestari Windy Puspitasari (Universitas Airlangga, 2019)
Universal precaution is a precautionary guidance on infection prevention that is expected to reduce the risk of transmission infection from patient to health worker regardless of the status infection. The purpose of this research is analyze the correlation between intention with compliance universal precaution application to nurses. This research is an observational study with cross-sectional design. Respondents in this study were nurses from 9 rooms who served in inpatient installations with total of 47 people. The sampling technique using simple random sampling. The data was collected by using questionnaires and observation. Analysis data used analysis of chi-square and Cramer’s V correlation. Universal precaution observed was hand washing, use of Personal Protective Equipment, management of sharp objects, and management of medical waste. The results showed that the majority of nurses (74.5%) were well behaved in compliance of universal precaution application. Statistical analysis show that there is a relationship between intention and compliance to the application of universal precaution (0.001) and strong correlationin in medium category (0.526). The conclusion was that the better of intention, the better the nurse compliance level in the application of universal precaution.Keywords: compliance, intention, universal precaution